Penerapan Metode Diskusi Untuk Meningkatkan Aktivitas Siswa Pada Pembelajaran Menirukan Pembacaan Pantun Anak Di SD Kelas IV Negeri 33 Melaban Pedini Kabupaten Sintang Provinsi Kalbar - Marlina Marlina (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Indonesian language learning using the discussion method has been implemented at SDN 19 Kepahiang in the 2020/2021 academic year with a total of 20 students. This research aims to increase student activity in learning to imitate reading children's rhymes using the discussion method. This research was carried out in three cycles, namely planning, implementing actions, and reflecting. The data collection techniques used are observation and tests. The application of the discussion method has been proven to increase student learning achievement, courage, express opinions, and train students to argue.